Integrated system to produce updated-estimates of the cost of adaptation to climate change in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The innovation (the new models and their outputs) were used to share updated adaptation estimates with the Gates foundation and Global commission on adaptation for their use in planning funding for agricultural research and development.